Statistical Analysis and Reflection on Domestic and Foreign Standards in the Field of Gears - Li Haixia; Zhi Yanfeng; Fan Ruili; Yu Feipeng; Guan Hongjie; Liu Zhongming (Jixie chuandong)
The main responsibilities, standardization fields and current centralized standards of standardization technical committees in the domestic and foreign gear industry are summarized. The corresponding relationship between the number of standards in different technical fields and the year of publication is statistically analyzed. The standardization technical elements of standards at different levels in China are also analyzed, and the development trend of gears related technologies is analyzed. In response to several new changes in China's standardization work in the new era, new requirements for the standardization work in the gear industry are proposed from both opportunities and challenges.